Increasing global agricultural production by reducing ozone damages via methane emission controls and ozone‐resistant cultivar selection. (5th February 2013) - Avnery, Shiri; Mauzerall, Denise L.; Fiore, Arlene M.
Abstract: Meeting the projected 50% increase in global grain demand by 2030 without further environmental degradation poses a major challenge for agricultural production. Because surface ozone (O3 ) has a significant negative impact on crop yields, one way to increase future production is to reduce O3 ‐induced agricultural losses. We present two strategies whereby O3 damage to crops may be reduced. We first examine the potential benefits of an O3 mitigation strategy motivated by climate change goals: gradual emission reductions of methane (CH4 ), an important greenhouse gas and tropospheric O3 precursor that has not yet been targeted for O3 pollution abatement. Our second strategy focuses on adapting crops to O3 exposure by selecting cultivars with demonstrated O3 resistance. We find that the CH4 reductions considered would increase global production of soybean, maize, and wheat by 23–102 Mt in 2030 – the equivalent of a 2–8% increase in year 2000 production worth 3.5–15 billion worldwide (USD2000 ), increasing the cost effectiveness of this CH4 mitigation policy. Choosing crop varieties with O3 resistance (relative to median‐sensitivity cultivars) could improve global agricultural production in 2030 by over 140 Mt, the equivalent of a 12% increase in 2000 production worth 22 billion. Benefits are dominated by improvements for wheat in South Asia, where O3 ‐induced crop losses would otherwise be severe. Combining the two strategies generates benefits that are less than fully additive, given the nature of O3 effects on crops. Our results demonstrate the significant potential to sustainably improve global agricultural production by decreasing O3 ‐induced reductions in crop yields.